Автоматизація розв’язування задач з планіметрії, записаних природною українською мовою - Жежерун, О.П.; Смиш, О.Р. (Проблеми програмування, 2020)
У роботі досліджено й описано створення системи для розв’язування задач з планіметрії за допомогою сучасних можливостей обробки природної української мови та розробленої сукупності алгоритмів опрацювання тексту задачі. Розробка базується на аналізі текстів планіметричних задач та аналізі доступних засобів обробки живої української мови, що наразі наявні. Результатом роботи є кінцевий програмний продукт, написаний мовою Python, що дає змогу вирішувати прості завдання з планіметрії The article focuses on developing a software solution for solving planimetry problems that are written in Ukrainian. We discuss tendencies and available abilities in Ukrainian natural language processing. Presenting a comprehensive analysis of different types of describing a problem, which shows regularities in the formulation and structure of the text representation of problems. Also, we demonstrate the similarities of writing a problem not only in Ukrainian but also in Belarusian, English, and Russian languages. The final result of the paper is a system that uses the morphosyntactic analyzer to process a problem’s text and provide the answer to it. Ukrainian natural language processing is growing rapidly and showing impressive results. Huge possibilities appear as the Gold standard annotated corpus for Ukrainian language was recently developed. The created architecture is flexible, which indicates the possibility of adding both new geometry figures and their properties, as well as the additional logic to the program. The developed system with a little reformatting can be used with other natural languages, such as English, Belarusian or Russian, as the algorithm for text processing is universal due to the globally accepted representations for presenting such types of mathematical problems. Therefore, the further development of the system is possible.